In situ occurrence of shale oil in micro-nano pores in Permian Lucaogou Formation in Jimsar Sag, Junggar Basin - Jin LIU; Jian WANG; Baozhen ZHANG; Jian CAO; Ling SHANG; Xiaogang ZHANG; Guijun WANG (Shiyou shiyan dizhi, 2022)
The development of micro-nano pores and throats in shale oil reservoirs has made it complicated and diversified for the occurrence and state of oil, and is difficult to be studied. A case study was carried out with the Middle Permian Lucaogou Formation in the Jimsar Sag of Junggar Basin by the approaches of Field Emission Scanning Electron Microscopy (FESEM), Nuclear Magnetic Resonance (NMR), Laser Scanning Confocal Microscope (LSCM) and nano-CT. The plane porosities of siltstones and dolomitic siltstones in sweet spots of the study area range from 11.0% to 23.5%, and the dissolved pores and intragranular dissolved pores larger than 2 μm account for more than 49.0%. The distribution of oil and pore water has strong differentiation in micro-nano scale, which is controlled by complex factors such as overpressure migration of hydrocarbon generation, pore surface adsorption and oil quality difference in different stages of continuous shale oil accumulation. In sweet spot reservoirs, intermediate oil and free water occur in the center of pores larger than 2 μm, while heavy oil exists on pore surface as thin film. Pores with the size smaller than 2 μm are mainly filled with heavy oil. Intermediate oil is relatively easier to be explored, while heavy oil is a more realistic and feasible target for enhanced oil recovery in the future.